Effects of a single bout of power exercise training on ambulatory blood pressure in older adults with hypertension: A randomized controlled crossover study. (November 2020) - Schimitt, Renato P; O Carpes, Leandro; Domingues, Lucas B; Tanaka, Hirofumi; Fuchs, Sandra C; Ferrari, Rodrigo
Highlights: Power training emerges as an advantageous practice for the elderly population. Power training exercises can acutely decrease blood pressure in older adults with hypertension. Post-exercise hypotension may be sustained under ambulatory conditions only for diastolic BP. Abstract: Objective: To evaluate the effect of a single bout of power exercise training (PT) on office and ambulatory blood pressure (BP). Methods: Twenty-four older adults with essential hypertension participated in two experimental sessions in a randomized order: the PT composed of 3 sets of 8–10 repetitions in 5 power training exercises and the non-exercise control at seated rest (Con). Both experimental sessions lasted 40 min. Office BP was measured continuously for 1 h in the laboratory and 24 h BP through ambulatory blood pressure monitoring. Results: Compared with Con, office systolic/diastolic BP decreased after PT (Systolic BP: 10 mmHg, p < 0.001; Diastolic BP: 4 mmHg, p = 0.015). A trend toward decrease (p = 0.06) was found in diastolic ambulatory BP during daytime (2 mmHg; p = 0.062) and nighttime (3 mmHg; p = 0.063) after PT. No differences were found between PT and Con sessions for systolic and mean ambulatory BP. Conclusion: A single bout of PT decreases office BP but this hypotensive effect is not sustained under ambulatory conditions in older patients with essential hypertension.